2021
DOI: 10.1002/jsp2.1149
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 mediates cell damage induced by hyperphysiological compression and regulates COX2/PGE2 in intervertebral discs

Abstract: Background Aberrant mechanical loading of the spine causes intervertebral disc (IVD) degeneration and low back pain. Current therapies do not target the mediators of the underlying mechanosensing and mechanotransduction pathways, as these are poorly understood. This study investigated the role of the mechanosensitive transient receptor potential vanilloid 4 (TRPV4) ion channel in dynamic compression of bovine nucleus pulposus (NP) cells in vitro and mouse IVDs in vivo. Methods Degenerative changes and the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In a mouse model, TRPV4 regulated the expression of COX2/PGE2, which in turn promoted cell-mediated loss of physiological function induced by excessive dynamic compression of the disc. The authors suggested that targeted TRPV4 inhibition may provide a new approach to treat patients suffering from intervertebral disc pathologies caused by excessive mechanical stress [53]. In addition, cyclic-tensile-strain-induced expression of the proteoglycans Acan and Prg4 in annulus fibrosus cells was abrogated after pharmacological inhibition of TRPV4.…”
Section: Trpv4 Is Sensitive To Tissue Mechanics In Diverse Processesmentioning
confidence: 99%
“…In a mouse model, TRPV4 regulated the expression of COX2/PGE2, which in turn promoted cell-mediated loss of physiological function induced by excessive dynamic compression of the disc. The authors suggested that targeted TRPV4 inhibition may provide a new approach to treat patients suffering from intervertebral disc pathologies caused by excessive mechanical stress [53]. In addition, cyclic-tensile-strain-induced expression of the proteoglycans Acan and Prg4 in annulus fibrosus cells was abrogated after pharmacological inhibition of TRPV4.…”
Section: Trpv4 Is Sensitive To Tissue Mechanics In Diverse Processesmentioning
confidence: 99%
“…TRP channels are non-selective calcium-permeable transmembrane channels that can be activated by different stimuli, including changes in temperature, pH, osmolarity, as well as oxidative and mechanical stress, either directly by mechanical forces applied to the cell membrane or indirectly via multistep signaling cascades that induce conformational changes, which in turn generate mechanical force on the cell membrane (Walter et al, 2016;Krupkova et al, 2017;Franco-Obregón et al, 2018;Kameda et al, 2019;Sadowska et al, 2019). The TRP vanilloid 4 (TRPV4) ion channel was recently identified as a mediator of stretchinduced inflammation and compression-induced cell damage and degeneration in IVD cells and tissues in the context of hyperphysiological mechanical loading (Cambria et al, 2020a;Cambria et al, 2021).…”
Section: Mechanosensing and Mechanotransductionmentioning
confidence: 99%